2015
DOI: 10.3844/ajessp.2015.427.439
|View full text |Cite
|
Sign up to set email alerts
|

Status of Heavy Metals in Water and Sediment of the Meghna River, Bangladesh

Abstract: Abstract:The pollution of river water and sediments by heavy metals has assumed serious problems due to their toxicity and accumulative behavior. The present study has been undertaken to assess the levels of heavy metals and the extent of pollution in the surface water and sediments from the Meghna river. Water and sediment samples were collected by the Standard Methods and, processed and analyzed for heavy metals using Flame Atomic Absorption Spectrophotometer (FAAS). The mean concentrations of heavy metal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 34 publications
6
25
1
Order By: Relevance
“…The results of heavy metal concentrations in surface water is shown in Table 2. The comparison of present findings with other national and international rivers is shown Table 3, where the present findings is compared with those from past research [22][23][24][25][26][27][28]. The average concentration of studied metals followed the decreasing order: Cr > Zn > Cu > Pb > Cd > Ni > As.…”
Section: Results and Discussion Distribution Of Metals In Different Ssupporting
confidence: 57%
“…The results of heavy metal concentrations in surface water is shown in Table 2. The comparison of present findings with other national and international rivers is shown Table 3, where the present findings is compared with those from past research [22][23][24][25][26][27][28]. The average concentration of studied metals followed the decreasing order: Cr > Zn > Cu > Pb > Cd > Ni > As.…”
Section: Results and Discussion Distribution Of Metals In Different Ssupporting
confidence: 57%
“…The concentrations exceeded the permissible limit set by WHO (2008), USEPA (1999) and FAO (1985). It is suggested that the concentration Al and Mn originated from the lithogenic and is also associated with spinning miles and paint industries wastes (Rahman et al 2014;Hassan et al 2015). The concentration of Zn varied from 32.78 to 81 mg/ kg.…”
Section: Seasonal Variation Of Heavy Metal Levels In Surface Sedimentmentioning
confidence: 99%
“…Hg concentration was recorded below the detection limit in all sediment samples in all seasons. A higher concentration of these metals was affected by discharges of textile and paint industries and domestic sewage waste (Datta and Subramanian 1998;Balkis et al 2010;Ergul et al 2008;Ahmad et al 2010;Saha and Hossain 2011;Ahmed et al 2012;Hassan et al 2015).…”
Section: Seasonal Variation Of Heavy Metal Levels In Surface Sedimentmentioning
confidence: 99%
“…The permissible level of DO, COD and BOD indicates that the lower dumping of organic wastes and lower aerobic bacterial decomposition has been occurred in those rivers. A very recent study showed that COD level (20.84-114.6) in the Meghna river is higher than permissible level [15]. This is may be occurred due to the transboundary water flow from polluted Buriganga and Shitalakkhya river into the Meghna river.…”
Section: Organic Pollutionmentioning
confidence: 98%
“…The use of this water may highly risk for sore on skin. The river Buriganga [8] Turag [9,25] Shitallakhya [10,26] and Meghna [15] are highly polluted which is indicated by higher level of COD value.…”
Section: Organic Pollutionmentioning
confidence: 99%